Meaning Variations of Qāla (قال) in Indonesian Language - Khoirin Nikmah (Izdihar : Journal of Arabic Language Teaching, Linguistics, and Literature, 2019)
One of main component for every language is verb. In Arabic, qāla (قال) is one of verbs which substantively is used in many oral and written language due to its wide meaning. This research focuses on meaning variation of qāla (قال) when it was translated into Indonesian. In this study, differential meaning can be caused by differential speaker and also differential context. Thereby, the research aims to classify and explain every single meaning of qāla (قال) verb. This descriptive qualitative research uses observation method with tapping technique. Meanwhile, the data was analyzed by translational method, referential method, and pragmatics method. The result of the research shows that; (1) There are three differential meanings of qāla (قال) according to speaker perspective, as well as ‘berfirman’, ‘bersabda’, and ‘berkata’. (2) There are some differential meanings of qāla (قال) according to linguistics perspective, such as ‘berkata, mengatakan, mengabarkan, mengumumkan, berbicara, mengucapkan, mengaku, pendapat, bertanya, menjawab, perintah, and berdoa.